2005
DOI: 10.1111/j.1467-8535.2005.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphing images: a potential tool for teaching word recognition to children with severe learning difficulties

Abstract: Children with severe learning difficulties who fail to begin word recognition can learn to recognise pictures and symbols relatively easily. However, finding an effective means of using pictures to teach word recognition has proved problematic. This research explores the use of morphing software to support the transition from picture to word recognition. Morphing software was used to teach word recognition to a group of eight children who were previously unable to recognise words. At the end of 16 teaching ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…In terms of cuing the correct word, the photographs worked well but, when used in the MM morphing, they were not efficient in leaving the child able to name the word without pictorial cues. This is in line with previous research in which pictorial cues are found to be readily recognised (Solman and Singh 1992), can be manipulated to become as effective as words alone (Sheehy 2005;Wu and Solman, 1995) but are not as effective in developing uncued recognition as HT (Sheehy 2002b). It has been argued that this performance reflects pictorial cues inefficiency in developing local feature recognition (Sheehy and Howe 2001).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In terms of cuing the correct word, the photographs worked well but, when used in the MM morphing, they were not efficient in leaving the child able to name the word without pictorial cues. This is in line with previous research in which pictorial cues are found to be readily recognised (Solman and Singh 1992), can be manipulated to become as effective as words alone (Sheehy 2005;Wu and Solman, 1995) but are not as effective in developing uncued recognition as HT (Sheehy 2002b). It has been argued that this performance reflects pictorial cues inefficiency in developing local feature recognition (Sheehy and Howe 2001).…”
Section: Discussionsupporting
confidence: 89%
“…It is debatable whether the outcomes for the two 'paper' conditions (WA and HT) would have been different if presented via a computer screen. Previous research has controlled this in a direct comparison of on-screen WA and MM and obtained findings in line with those obtained here (Sheehy 2005). It is also important to consider the overall purpose of the research, which is to identify an effective teaching approach which can be used in the classroom.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations